Does the Role of Career Adaptability and Career Development Influence Employee Performance at Legal Universitas Negeri Semarang - Mursidah, Siti; Khoiruddin, Moh; Septantri, Lidiadni (Management Analysis Journal, 2024)
This study aims to examine the role of Career Adaptability and Career Development in enhancing employee performance within the context of higher education transformation. Research focusing on organizations undergoing continuous change remains limited. Change management is a critical issue for such organizations. Universitas Negeri Semarang (UNNES), as an example of higher education undergoing structural transformation into a Legal Entity State University (PTN-BH), serves as the context for this study. Specifically, this research explores the impact of career adaptability on employee performance at UNNES. Currently, there is a lack of research on career development that specifically focuses on higher education institutions transitioning to PTN-BH. Key issues addressed in this study include career dynamics within continuously evolving organizations. The research adopts a quantitative approach with a causal design. The  sampling  technique  in  this  study  is  using random sampling where sampling is done randomly regardless of the strata in the population.  The  sample  of  this  study  amounted  to  138  people  (20%)  of  all employees of Universitas Negeri Semarang. In this study, surveys were used as a method of data collection. Data analysis techniques in this study used descriptive and statistical methods. The findings of this study indicate that the factor that plays a role in influencing employee performance at Universitas Negeri Semarang is career adaptability. Meanwhile, career development does not influence  employee  performance.  Meanwhile,  career  adaptability  and  career development together have a significant impact on performance. Thus, employee adaptability with a comfortable work environment designed to build trust between employees,  share  knowledge  and  skills  to  support  continuous  learning  and improve employee performance is needed.